ESTIMATED OF GENETIC AND NON GENETIC PARAMETERS FOR DAILY TEST MILK YIELD AND FAT PERCENTAGE IN HAMDANI EWES - Al-Barzinji Y. M (Mesopotamia Journal of Agriculture)
This experiment was included 655 test-days for milk yield and fat percentage in Hamdani ewes obtained from 56 ewes raised at Grdarasha station- College of Agriculture, Salahaddin University during period from 2001 t0 2002. The daily milk yield showed to be highest at 6, 8 and 10 weeks after lambing. The mean daily milk yield and fat % were 440.10 gm and 5.94% respectively. The estimated repeatability for milk yield and fat% were 0.40 and 0.19, respectively and BLUP values ranged from -265.11 to 708.46 gm and -1.23 to 1.44 % for milk yield and fat%, respectively. Sex of lamb, age of dam and series of the tests have a significant (p≤0.01) influence on the daily milk yield. Type of birth had no significant effect on milk yield. On the other hand, type of birth and series of the tests have a significant (p≤0.01) influence on fat %. The highest fat % was found to be during 12-15th tests.